Arizona Essential Skills for Mathematics. Reformatted Edition - Arizona State Dept. of Education, Phoenix; Arizona State Dept. of Education, Phoenix ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
This document ties the essential skills needed in mathematics to the National Council of Teachers of Mathematics' (NCTM) Curriculum and Evaluation Standards to help facilitate future curriculum development. The overall goal for the 21st century is to make mathematical power a reality for all students. The rationale for this document can be found in three goals: (1) to restructure mathematics curricula and teaching strategies to change mathematics from a static discipline to a dynamic process; (2) to set high standards of numeracy for all students; and (3) to integrate student assessment with the learning process. This document divides essential mathematical skills into three grade levels: K-3, 4-8, and 9-12. Each section presents the essential skills needed at each level in matrix form showing the direct relationship between the content skills and the NCTM Standards. Each section also supplies a list of student outcomes for each content area, as well as examples of indicators. A direct assessment program which can be used in meeting goal 3 is presented. Contains 22 references. (RLB)
Availability: Arizona State Dept. of Education, 1535 W. Jefferson, Phoenix, AZ 85007.
ERIC Note: For earlier edition, see ED 325 364.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Algebra; Calculus; Curriculum Development; Educational Assessment; Educational Objectives; Elementary Secondary Education; Fractions; Geometry; Mathematical Applications; Mathematical Concepts; Mathematical Logic; Mathematics Curriculum; Mathematics Education; Mathematics Skills; Measurement; Numeracy; Probability; Problem Solving; State Standards; Statistics; Student Evaluation; Trigonometry; Arizona; Mathematical Communication -- Mathematical Thinking -- NCTM Curriculum and Evaluation Standards; Guides, Classroom -- Teacher